EFEKTIFITAS PEMBELAJARAN MATEMATIKA MODEL LEARNING CYCLE 5E BERBANTUAN CD INTERAKTIF MATERI SEGITIGA KELAS VII DI SMPN 2 LIMPUNG KABUPATEN BATANG - Lilik Ariyanto; Muhammad Prayito (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2012)
This study has the objective to determine the effectiveness of mathematic learning with Learning Cycle 5e model using interactive CD of triangle in class VII N 2 Limpung, Batang . This type of research is experimental research. Variables used in this study were: (1) student learning outcomes, obtained with the test, (2) creativity of student learning obtained from observations. The results of field trials demonstrated experimentally achieve effective classroom learning include, (1) study completed by the Z = -1.48 classical individually and with one test sample value sig (2-tailed) is 0.016, (2) creativity affects the outcome learning seen from the R square in Model Summary table obtained 0.660 = 66%., and (3) there is a difference between a class to learn the results of experimental and control classes with values ​​in the table Independent sig Test Samples of 0.029 = 2.9%, the average value the average grade of 70.57 experimental and control classes for 60.93 it can be concluded that the experimental class learning better learning outcomes compared to the control class.